NON-PATHOGENIC PHYLLOSPHERE BACTERIA PRODUCING BIOACTIVE COMPOUNDS AS BIOLOGICAL CONTROL OF Xanthomonas oryzae pv oryzae - NI PUTU RATNA AYU KRISHANTI; ARIS TRI WAHYUDI; ABDJAD ASIH NAWANGSIH (International Journal of Pharma and Bio Sciences, 2015)
Xanthomonas oryzae pv oryzae (Xoo) is the causal agent of leaf blight disease of rice. The use phyllosphere bacteria of rice plant as biocontrol agent is an alternative ecofriendly strategy to control Xoo. The aims of this study were to isolate and screen phyllosphere bacteria of rice plant which has an ability to produce bioactive compounds against Xoo. A total of 400 phyllosphere bacterial isolates were obtained from rice plant leaves, 171 isolates produced bioactive compounds that inhibited Xoo, and 79 isolates performed negative response of hypersensitivity on tobacco leaf and 57 isolates among them showed negative pathogenicity on rice leaf. Molecular identification based on 16S rRNA genes of nine non-pathogenic isolates revealed that 6 isolates were identified as genus Bacillus, whereas isolates BFF62, BFV63, and BFF75 were identified as Myroides odoratimimus, Pontibacter niistensis, and Delftia tsuruhatensis, respectively. Isolate BFF84 that showed the highest anti-Xoo activity was identified as Bacillus aerophilus